Lagged and simultaneous effects of exposure to violence at home on child-to-parent violence: gender differences - Cano-Lozano, M. Carmen; Navas-Martínez, María J.; Contreras, Lourdes (Frontiers in Psychiatry, 2024)
Introduction. Numerous studies have found that exposure to violence at home is a risk factor for child-to-parent violence. However, most of the available studies do not delimit a time frame for exposure to violence. This aspect is fundamental to differentiating lagged effects (compensation) from simultaneous effects (reciprocal). The purpose of this study is to clarify the relationship between lagged (before the age of 10) and simultaneous (last year) exposure to violence at home (direct victimization: parent-to-child violence and vicarious victimization: exposure to violence between parents) and childto-parent violence, the possible differential reactive or instrumental motivation of these relationships and whether they differ based on the gender of children and parents. Method. The sample comprised 1,734 Spanish adolescents who lived with both parents (57.3% girls), aged between 13 and 17 years. The instruments used were the Child-to-Parent Violence Questionnaire and the Violence Exposure Scale. Results. Positive and significant relationships were found between child-to-parent violence and exposure to violence at home both during childhood and during the last year; however, the relationships were stronger in the latter. The most important predictors were direct parental victimization during the last year. Boys exerted more reactive violence toward the father concerning exposure to violence by the father toward the mother during the last year. In the case of girls, violence toward both father and mother is more reactive to most victimization experiences. Conclusions. The findings highlight the need to intervene in family contexts of violence to prevent child-to-parent violence.